CACNA1H missense mutations associated with amyotrophic lateral sclerosis alter Cav3.2 T-type calcium channel activity and reticular thalamic neuron firing. Issue 6 (1st November 2016) - Rzhepetskyy, Yuriy; Lazniewska, Joanna; Blesneac, Iulia; Pamphlett, Roger; Weiss, Norbert
ABSTRACT: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease that affects nerve cells in the brain and the spinal cord. In a recent study by Steinberg and colleagues, 2 recessive missense mutations were identified in the Cav 3.2 T-type calcium channel gene ( CACNA1H ), in a family with an affected proband (early onset, long duration ALS) and 2 unaffected parents. We have introduced and functionally characterized these mutations using transiently expressed human Cav 3.2 channels in tsA-201 cells. Both of these mutations produced mild but significant changes on T-type channel activity that are consistent with a loss of channel function. Computer modeling in thalamic reticular neurons suggested that these mutations result in decreased neuronal excitability of thalamic structures. Taken together, these findings implicate CACNA1H as a susceptibility gene in amyotrophic lateral sclerosis.